Safeguarding human and environmental rights in agricultural supply chains – A risk management toolkit - Charry, Andres; Wiegel, Jenny; Siles, Pablo; Claros, Luisa; Nguyen, Thuy Thanh; Nguyen, Mai; Talsma, Tiffany (2024)
There is growing agreement that companies at the head of global agricultural supply chains should take greater responsibility for addressing the negative effects of their commercial activities at origin, for example on human and labor rights or environmental degradation. Yet how to do this in a practical but rigorous way, that generates timely and actionable information is not simple. Negative behaviors (i.e. labor violations) are often hidden, and hard to quantify. Companies have limited capacity for data collection and analysis. To respond to these challenges, the Alliance, FMO and Mercon Coffee Group developed a Supply Chain Risk Assessment and Management Toolkit, which takes a root causes approach to understanding environmental and social risks in supply chains. We used the toolkit to assess country-level risks for nine coffee origins.